Development Of Motor Ability In Children With Low Birth Weight History In Mamuju District - Supratti Supratti; Iqra S (Jurnal Kesehatan Prima, 2020)
Improving the quality of Human Resources (HR) through stimulation of growth and development in children aged under two years (0-24 months), needs to be a priority concern of parents / caregivers considering this period is called the "golden age" or golden period, because brain development is very fast at two year old baby / BADUTA. Low Birth Weight (LBW) infants are at risk of growth and development disorders if LBW treatment and stimulation of development are not optimal and continuous. The research objective was to determine the development of Baduta motor skills with a history of LBW in the Regency. Descriptive research with the Cross Sectional Study approach. The study population was all Baduta with a history of LBW in Mamuju District, Mamuju District. The sample of this study was Baduta who had a history of low birth weight birth and lived in Mamuju District. the number of samples is 28 million, using the KPSP Pre Srining Development Questionnaire (KPSP) measuring gross motor development and fine motor development. The results showed that there were still 11 baduta (39.3%) unable to do gross motor skills and 5 baduta (17.9%) unable to do fine motor skills